2003
DOI: 10.1258/000456303322326371
|View full text |Cite
|
Sign up to set email alerts
|

Analytical and clinical aspects of adrenocorticotrophin determination

Abstract: Adrenocorticotrophin (ACTH) is formed from the cleavage of pro-opiomelanocortin. Measurement of plasma ACTH is a key step in the differential diagnosis of hypothalamic-pituitary-adrenal disorders.Prior to the development of radioimmunoassay, the bioassays employed for the determination of ACTH were highly complex, time-consuming and costly in terms of number of animals used. Their sensitivity was such that the normal early morning peak of ACTH could not be determined. The introduction of immunoassay methodolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 67 publications
1
49
0
1
Order By: Relevance
“…The ACTH assay we used in our study employs two monoclonal antibodies specific for ACTH [9][10][11][12] and for the C-terminal region (ACTH 36-39). Due to common antigenic structure, the antibodies recognize intact biologically active ACTH 1-39 and the ACTH precursors POMC and pro-ACTH [1]. Enzymatic cleavage or modification of ACTH may have occurred, even in the presence of aprotinin, at other sites in the mol- As expected, for each of the three study conditions we observed a decreasing trend of measured ACTH concentrations with time.…”
Section: Resultssupporting
confidence: 73%
See 2 more Smart Citations
“…The ACTH assay we used in our study employs two monoclonal antibodies specific for ACTH [9][10][11][12] and for the C-terminal region (ACTH 36-39). Due to common antigenic structure, the antibodies recognize intact biologically active ACTH 1-39 and the ACTH precursors POMC and pro-ACTH [1]. Enzymatic cleavage or modification of ACTH may have occurred, even in the presence of aprotinin, at other sites in the mol- As expected, for each of the three study conditions we observed a decreasing trend of measured ACTH concentrations with time.…”
Section: Resultssupporting
confidence: 73%
“…Analysis of plasma adrenocorticotropin (ACTH) is a key step in differentiating hypothalamic-pituitary-adrenal disorder diagnosis and of great clinical significance for both Cushing's syndrome and adrenal insufficiency [1]. ACTH in the blood is considered highly unstable because of proteolytic degradation [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two of these preparations, from the National Hormone and Pituitary Program and the National Institute for Biological Standards and Control (code 74/ 555), have similar immunoreactivity but differ significantly in biological potency. 121 In the absence of an agreed international standard for ACTH, it is difficult to draw conclusions regarding assay bias. The predominant assay method in use in the UK is the Siemens Immulite.…”
Section: Standardization and Bias/accuracymentioning
confidence: 99%
“…In fact, various immunoassays were proposed for the determination of ACTH based on different antibodies and using radioactivity, chemiluminiscence or fluorescence as detection techniques. These methodologies allowed ranges between a few units up to various hundreds of ng/L ACTH to be covered [19][20][21], concentrations that are much larger than those appearing in the linear range obtained for this hormone with the developed Strept-AP/ Biotin-ACTH/anti-ACTH/APBA/SPCE1 immunosensor. On the other hand, the electrochemical immunosensor for ACTH previously described by our group provided a detection limit of 18 pg/L [15].…”
Section: Analytical Characteristics For Acth and Cortisolmentioning
confidence: 99%